2015
DOI: 10.1111/ane.12451
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adjunctive lacosamide treatment in patients with partial-onset seizures

Abstract: In eligible patients who entered the open-label extension trial, lacosamide was generally well tolerated. For most patients within each yearly completer cohort, seizure reduction was maintained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
38
4
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 12 publications
12
38
4
5
Order By: Relevance
“…Moreover, these retention rates are also consistent with the 59.3% retention rate at 1 year described in a study of 59 adults receiving lacosamide in adjunctive use 18. When comparing to Kaplan‐Meier estimates the 1‐year retention rates in our study are higher than those described in another long‐term follow‐up study with lacosamide in adjunctive use (74.5% Kaplan‐Meier estimates) 19. However, this may be due to the less severe patient population included into our study.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, these retention rates are also consistent with the 59.3% retention rate at 1 year described in a study of 59 adults receiving lacosamide in adjunctive use 18. When comparing to Kaplan‐Meier estimates the 1‐year retention rates in our study are higher than those described in another long‐term follow‐up study with lacosamide in adjunctive use (74.5% Kaplan‐Meier estimates) 19. However, this may be due to the less severe patient population included into our study.…”
Section: Discussionsupporting
confidence: 90%
“…2,3 Efficacy and safety of lacosamide as adjunctive therapy were established in three randomized, double-blind, placebo-controlled trials. [7][8][9] Monotherapy approval of lacosamide in the EU was based on the results of a large-scale, double-blind trial, which demonstrated that lacosamide was noninferior to controlledrelease carbamazepine (carbamazepine-CR) and was well tolerated as first-line monotherapy in patients with newly diagnosed epilepsy. [7][8][9] Monotherapy approval of lacosamide in the EU was based on the results of a large-scale, double-blind trial, which demonstrated that lacosamide was noninferior to controlledrelease carbamazepine (carbamazepine-CR) and was well tolerated as first-line monotherapy in patients with newly diagnosed epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In the 3 long‐term extension studies, efficacy was assessed within the “yearly completer cohort.” As expected, the responder rates increased over time because, according to this design, efficacy was assessed only in those individuals remaining on LCM for 1‐5 years, thus did not reflect the efficacy profile of LCM in the real world.…”
Section: Discussionmentioning
confidence: 99%